2015
DOI: 10.1111/jipb.12336
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and molecular cloning of a serine hydroxymethyltransferase 1 (OsSHM1) in rice

Abstract: Serine hydroxymethyltransferase (SHMT) is important for one carbon metabolism and photorespiration in higher plants for its participation in plant growth and development, and resistance to biotic and abiotic stresses. A rice serine hydroxymethyltransferase gene, OsSHM1, an ortholog of Arabidopsis SHM1, was isolated using map-based cloning. The osshm1 mutant had chlorotic lesions and a considerably smaller, lethal phenotype under natural ambient CO2 concentrations, but could be restored to wild type with normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 38 publications
(49 reference statements)
5
28
0
Order By: Relevance
“…In addition, serine hydroxymethyltransferase (SHMT) is an essential component of photorespiration. A previous study found that an osshm1 mutant exhibited chlorotic lesions and a lethal phenotype ( Wang et al, 2015 ). Lin et al (2012) found that OsCATC could increase hydrogen peroxide in leaves, which consequently promoted NO production and led to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, serine hydroxymethyltransferase (SHMT) is an essential component of photorespiration. A previous study found that an osshm1 mutant exhibited chlorotic lesions and a lethal phenotype ( Wang et al, 2015 ). Lin et al (2012) found that OsCATC could increase hydrogen peroxide in leaves, which consequently promoted NO production and led to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The Arabidopsis mitochondrial SHMT is encoded by AtSHM1 and is required for the proper functioning of photorespiration (Somerville and Ogren, 1981;Voll et al, 2006). Its ortholog in rice (Oryza sativa) is OsSHM1 (Wang et al, 2015;Wu et al, 2015). AtSHM3 (Zhang et al, 2010) encodes an SHMT protein that is targeted to plastids, and AtSHM7 encodes an SHMT that is a nonfunctional enzyme and is found to be required for SAM biosynthesis in the nucleus and that epigenetically affects sulfur homeostasis .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies indicated that overexpression of Lsi1 in chilling-sensitive Dular rice results in enhanced tolerance to low temperature; gene expression of OsSHMT was up-regulated in the Lsi1-OX rice in comparison with Dular rice [6]. Wang et al [13] found that OsSHMT is localised in the mitochondria, and it has also been reported to localise in the chloroplast, cytoplasm, nucleus, plasma membrane and cytosol [25,26]; despite these results, our present study indicated that OsSHMT is also localised in the endoplasmic reticulum, which is the main organelle for protein and lipid synthesis, membrane biogenesis, xenobiotic detoxification and cellular calcium storage [27]. [28].…”
Section: Discussionmentioning
confidence: 99%